REFORMULASI HUKUM PERCERAIAN PEGAWAI NEGERI SIPIL DALAM PENYETARAAN HAK PRIVAT WARGA NEGARA - Fenny Desy Fitria; Intan Cahyani; Janeke Kusherawati; Tiara Mardova (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The obligation of every civil servant to obtain permission from his superiors in the case of filing for divorce is the basic substance of PP No. 45 of 1990 concerning Amendments to Government Regulation Number 10 of 1983 concerning Marriage and Divorce Permits for Civil Servants. The regulation was formulated to provide guarantees of procedural certainty for civil servants in divorce efforts, authorize superior officials to mediate, examine, and decide on permits or reject applications. With this effort, the government hopes that civil servants as state servants, role models for the community, can become more orderly, disciplined, and organized. However, the legalization of the obligation to obtain divorce permits is basically a reductionism to the private rights of civil servants as citizens and dualism of authority that collides with the court. Every citizen has the same position under the law. Civil servants have the right to file a lawsuit to the court and obtain a decision that has permanent legal force (inkrat) without having to first obtain a decision from the employer. The authority to mediate, examine, and obtain privacy information is the absolute authority of the court, and civil servants have the right to only provide them at the court. This study focuses on a juridical study of the legal rules for civil servants divorce, its potential and consequences for civil servants, as well as alternative solutions for improving future arrangements.